Bioprimee of seed with Bacillus Velezensis UTB96 to control the fungal pathogen of root and crown rot (Fusarium pseudograminearum) and improving some growth indicators of wheat - mohsen sasani; Masoud Ahmadzadeh; M.R. Jahansuz; sorayya navid (علوم و فناوری بذر ایران)
Root and crown rot of wheat is one of the most important diseases that caused by Fusarium species. The present study was conducted with the aim of seed Bioprime with bacteria to control fungal pathogens of root and crown rot and improving some growth indicators of wheat in laboratory and greenhouse conditions in 2019. The Effect of bacterial inhibition on fungal pathogen growth in vitro and in cross-culture test, metabolites and bacterial extracts were 60, 50 and 30 percent respectively. Bacterial isolates were able to produce biocontrol enzymes, metabolites and hormones of growth promoting such as auxin, siderophore, and ACC deaminase. In vitro, infection of wheat seeds before priming had a beneficial effect on increasing the efficiency of bioprime technique with bacteria, because in uninfected wheat seeds, bacteria did not play a role in reducing pathogenic fungi. Bioesmoprim, osmoprime and halloprime had the most impact in controlling the pathogenic fungus and improving the growth indices of wheat (germination percent, length and weight of root and stem) in greenhouse conditions, respectively. Although Talc powder and gum in germinated seeds reduced the fungal disease of root and crown rot, but seed germination percentage of wheat seeds were reduced, too. The combination of talc powder + xanthan gum with bacteria improved the mentioned traits.